2002
DOI: 10.1097/00002371-200203001-00005
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Interleukin-18 Against the Murine T-Cell Leukemia/Lymphoma EL-4 in Syngeneic Mice

Abstract: Interleukin (IL)-18 induces interferon (IFN)-gamma production by T cells and natural killer (NK) cells, and augments NK cell activity in mouse spleen cell cultures. It has recently been demonstrated that in vivo administration of IL-18 to mice results in considerable antitumor effects against syngeneic Meth A sarcoma. In this study, the antitumor effects of IL-18 against murine T-cell leukemia (EL-4) were evaluated. EL-4 proliferation was resistant in vitro to IL-18 and IFN-gamma. When 4 x 10(6) EL-4 cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…IL-18 has preventive activity against the development of murine T-cell leukemia/lymphoma EL-4 in syngeneic mice. 48 IL-18 strongly induces iNOS in natural killer cells via induction of IFN-␥ and TNF-␣. 49 However, activation of IL-18 is downregulated by iNOS activity because IL-18 is activated by IL-1␤-converting enzyme, which is inhibited by S-nitrosylation by NO.…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 has preventive activity against the development of murine T-cell leukemia/lymphoma EL-4 in syngeneic mice. 48 IL-18 strongly induces iNOS in natural killer cells via induction of IFN-␥ and TNF-␣. 49 However, activation of IL-18 is downregulated by iNOS activity because IL-18 is activated by IL-1␤-converting enzyme, which is inhibited by S-nitrosylation by NO.…”
Section: Discussionmentioning
confidence: 99%
“…Intercrossing TEL-JAK2 transgenic animals with TCRα -/-mice does not shift disease phenotype or latency (N. dos Santos and J. Ghysdael, personal communication). The situation for EL-4-induced lymphoma is less clear cut, because NK cells as well as CTLs have been reported to lyse EL-4 cells (33)(34)(35).…”
Section: Figurementioning
confidence: 99%
“…7 Recently, several reports have shown that IL-18 has potent antitumor effects when administered in animal models of lung cancer, breast cancer, sarcoma and melanoma in vivo. [7][8][9][10][11] In these models, systemic administration of IL-18 9,12 or in vivo IL-18 gene transfer 13,14 inhibited tumor growth and prolonged the survival of tumor-bearing mice. The antitumor effects of IL-18 in multiple animal models provided the rationale for investigation of recombinant human (rh) IL-18 in clinic cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%